Molecular characterization of XvPer1, a novel antioxidant enzyme from the resurrection plant Xerophyta viscosa, and AC3, a LEA-like protein from Arabidopsis thaliana - Mowla, Shaheen B (Department of Molecular and Cell Biology, 2014)
By differential screening of a cDNA library of the resurrection plant Xerophyta viscosa, a cDNA termed XvPer I was isolated for its over-expression under dehydration stress. Analysis of the cDNA sequence indicated a hydrophilic protein of a predicted Mw of 24.2 kDa with high identity to plant l-Cys peroxiredoxins, a novel antioxidant enzyme. Southern blot analysis revealed that XvPer I was most probably a single copy gene. The polypeptide sequence had significant identities (-70%) with other recently identified plant I-Cys peroxiredoxins with an absolutely conserved active site (PVCTTE). The protein sequence also had a putative bipartite nuclear localization signal.